Generalized maximum-entropy sampling. Issue 2 (2nd April 2020) - Lee, Jon; Lind, Joy
Abstract: We introduce the generalized constrained maximum-entropy sampling problem (GCMESP) as a common generalization of the ordinary constrained maximum-entropy sampling problem (CMESP) and the constrained D-optimality problem (CDOPTP). Exact algorithms for both CMESP and CDOPTP are based on branch-and-bound methods. We extend a spectral upper-bounding method for the CMESP to the GCMESP.